The binding of [3H]-tiotidine to homogenates of guinea-pig lung parenchyma. - Foreman, J. C. (1985)
By use of a rapid filtration assay, the binding of [3H]-tiotidine to homogenates of guinea-pig lung parenchyma was found to be saturable and of a high affinity. Mean values for the KD and Bmax were calculated as 8.5 +/- 1.5 nM and 28 +/- 5 fmol mg-1 protein respectively. The association and dissociation rate constants for [3H]-tiotidine binding at 4 degrees C were calculated to be 0.81 +/- 0.06 microM min-1 and 0.063 +/- 0.005 min-1 respectively, yielding a kinetically derived KD of 7.8 nM. A wide range of H2-receptor agonist and antagonists displaced [3H]-tiotidine binding from lung parenchyma homogenates in a biphasic manner. Examination of the first phase of the displacement of [3H]-tiotidine yielded Ki values for the antagonists tested similar to those found in other binding studies using this ligand and similar to KB values calculated for the antagonists in pharmacological studies.